Rebuilding the community: the Federation of Jewish Communities and American Jewish humanitarian aid in Yugoslavia, 1944–1952*. Issue 2 (3rd April 2017) - Kerenji, Emil
Abstract: This article recounts the implications of American Jewish aid for rebuilding the Jewish communities of Yugoslavia in the immediate aftermath of the Holocaust. By focusing on the founding and the activities of the Autonomous Relief Committee (ARC), which channelled aid provided by the American Jewish Joint Distribution Committee (JDC), the article argues that it was the power that ARC assumed, of deciding on funding priorities and being in close proximity to the new Yugoslav communist regime, that allowed it to shape the outlook of post-Holocaust Jewishness in Yugoslavia. The article is based primarily on previously unexamined sources from the Federation of Jewish Communities of Yugoslavia and JDC, and sheds new light on the dynamic period of negotiation of the new normative Jewish identity in the aftermath of the Holocaust.